If it's not what You are looking for type in the equation solver your own equation and let us solve it.
36=18+x
We move all terms to the left:
36-(18+x)=0
We add all the numbers together, and all the variables
-(x+18)+36=0
We get rid of parentheses
-x-18+36=0
We add all the numbers together, and all the variables
-1x+18=0
We move all terms containing x to the left, all other terms to the right
-x=-18
x=-18/-1
x=+18
| 4b=38-2(b+4) | | 28=3u+–20 | | 4x=-30-6x | | x2-14x+30=-3 | | 32=w-67 | | x+2=7x-16 | | 0=-16x^2-70x+49 | | 13+9+7+7=n | | -6x-7=54 | | 4b=38-2(b+4 | | 2x/3+x=90 | | 4/5b=32 | | 11=-k-5 | | 4(x+7)=2x+28+2x | | 13v+9+7+7=32 | | 3-2x5=1 | | -3+-3v=-12 | | 5x-15-7x=2x+34 | | 4x-4=52-3x | | 2y+8-5y=-28= | | 0.10m+3.95=23.75 | | -1=5x-8+3x | | 5+x3=2x8 | | 2(x-3)=16-3x | | 4(x-3)=49 | | 15x+3=x-6 | | 12+x=195 | | 4x+54=110 | | 20=k+1 | | r-4/8=r/6 | | 0.75(t-1)+4.25=5.75 | | n/8+7=-9 |